The Power of Economists Within the State 2017
DOI: 10.11126/stanford/9781503600492.003.0007
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Economists within the State

Abstract: The final chapter revisits the overarching argument about the varying power of economists within the state and its impact on the adoption of market-conforming policies. It points out that although economists often played a central role in tax reform processes, their influence depended crucially on the institutionalization of economic knowledge within the state in the postwar period. The chapter also considers what general lessons can be drawn from this analysis and discusses the future prospects for the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…The analysis of ideas and expertise in economic policymaking has now been the focus of a vast body of literature (Blyth [2002]; Christensen [2017]; Hall [1993], among others). Different approaches emphasise different factors to account for resilience and change in dominant ideas.…”
Section: Ideational Change and Resilience In Economic Policymakingmentioning
confidence: 99%
“…The analysis of ideas and expertise in economic policymaking has now been the focus of a vast body of literature (Blyth [2002]; Christensen [2017]; Hall [1993], among others). Different approaches emphasise different factors to account for resilience and change in dominant ideas.…”
Section: Ideational Change and Resilience In Economic Policymakingmentioning
confidence: 99%
“…The articles by Thiemann and by Ban and Patenaude also point to the ways in which pre‐crisis trends—in particular, those of scientization and rationalization—have conditioned post‐crisis changes in central banking. Indeed, both these contributions engage directly with the broader debate on the role of expertise in shaping the policy outcomes of public administrations (Christensen ). In Thiemann's analysis, the difficulty of implementing counter‐cyclical macroprudential policy is all the greater because of the importance placed within the central banking community on expertise and rigorous epistemological bases for risk analyses and policy tools.…”
Section: Contributionsmentioning
confidence: 99%
“…In a diverse set of cases and contexts, researchers have repeatedly found that the power of policy‐oriented experts to intervene in politics and influence policy depends, in large part, on the relationships they forge with policymakers and the positions they occupy vis‐à‐vis policymaking institutions or fields (Christensen, ; Fourcade, ; Hirschman & Berman, ; Medvetz, ; Mudge, ; Mudge & Vauchez, ). For example, the embeddedness of economists within the state apparatus has guaranteed the lasting and widespread influence of neoliberal economic theory and policy (Babb, ; Christensen, ; Fourcade, ; Fourcade‐Gourinchas & Babb, ). Likewise, think tank experts have been able to exert political influence by occupying positions between and proximate to the policy domains they ultimately influence (Medvetz, ).…”
Section: Plugging Into Policymentioning
confidence: 99%
“…Bureaucrats and policymakers committed to justice and equity may be especially likely in fields where former activists have entered state spaces and where policymakers think of their work as oriented toward democratic or just goals (e.g., Abers, ; Abers & Keck, ; Coslovsky, ; Friedmann, ). We may also encounter policymaking actors who identify with professional or political commitments that challenge their official charge (e.g., Christensen, ; Friedmann, ) or who have developed their own sociological and structural approach to understanding their work (e.g., Silbey, Huising, & Coslovsky, ). In other words, across policy domains sociologists may find partners that share their professional and normative commitments.…”
Section: Plugging Into Policymentioning
confidence: 99%